2023
DOI: 10.1186/s12905-023-02454-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and factors influencing modern contraceptive practice among tribal married women in India: evidence from National Family Health Survey 5 (2019–2021)

Abstract: Background The unmet need for family planning has been a public health concern in developing countries, especially in the south-east region. In India, the expanding roles of women has led to a growing need for family planning and contraception. However, tribal women still struggle with reproductive and sexual health issues. Unfortunately, most tribal women are not informed about the potential health risks associated with contraceptive use, as service providers often neglect to provide this info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Various similar studies have also been reported on the Indian subcontinent among different population groups, including tribal populations (Panda et al, 2023), (Hall et al, 2008), (Ghule et al, 2018), (Palo et A review of the literature reveals that barriers to the acceptance and use of modern FP methods and contraceptive use are still found at low utilization levels and are very unsatisfying among tribal populations; moreover, even a number of microlevel community-based studies have not been performed in diverse socioenvironmental settings. To ll this gap, the present study involved a qualitative investigation to obtain an in-depth understanding of the existing barriers to modern FP, contraceptive use, the management of unwanted pregnancies, and the spacing between two children among the Bonda, a particular vulnerable tribe group (PVTG), which is con ned to the restricted hill pockets of the Eastern Ghats Mountain Range located in the Malkangiri district of Odisha, India.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Various similar studies have also been reported on the Indian subcontinent among different population groups, including tribal populations (Panda et al, 2023), (Hall et al, 2008), (Ghule et al, 2018), (Palo et A review of the literature reveals that barriers to the acceptance and use of modern FP methods and contraceptive use are still found at low utilization levels and are very unsatisfying among tribal populations; moreover, even a number of microlevel community-based studies have not been performed in diverse socioenvironmental settings. To ll this gap, the present study involved a qualitative investigation to obtain an in-depth understanding of the existing barriers to modern FP, contraceptive use, the management of unwanted pregnancies, and the spacing between two children among the Bonda, a particular vulnerable tribe group (PVTG), which is con ned to the restricted hill pockets of the Eastern Ghats Mountain Range located in the Malkangiri district of Odisha, India.…”
Section: Introductionmentioning
confidence: 98%
“…Worldwide, among the 1.9 billion (15-49 years) women, 966 million who use any contraception methods are categorized as 874 million who have adopted a modern method and 92 million who have adopted a traditional contraceptive method (UNDESA, 2022). The National Family Health Survey 5 (NFHS-5), which was conducted between 2019 and 2021, reported that 53% of tribal married women in India use any modern contraceptive practices (i.e., below the national average), where more than 80% of the users receive FP-related information from health workers as well as from public health facilities (Panda et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The information is scarce and to the best of the authors' knowledge no large‐scale study in India has so far been carried out which has studied the contraceptive behavior of women post pregnancy loss. The existing literature details post abortion contraceptive behavior 21,22 but little is known about the contraceptive behavior of women whose pregnancy was otherwise terminated. The objective of this study was to describe the post pregnancy loss contraceptive behavior of Indian women in a reproductive age group using a recent nationally representative dataset.…”
Section: Introductionmentioning
confidence: 99%